2021
DOI: 10.1029/2021gl095651
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Multiple Ferrel‐Like Cells on Jupiter

Abstract: Over the last few decades, spacecraft and ground-based observations have gathered data about Jupiter's atmosphere, including measurements of cloud reflectance (

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 70 publications
(168 reference statements)
4
26
0
Order By: Relevance
“…This picture is usually connected to deep-shell simulations of rotating convection (e.g., Aurnou & Olson 2001;Christensen 2001;Heimpel et al 2005;Kaspi et al 2009;Gastine & Wicht 2012;Yadav & Bloxham 2020). It is consistent with cloud tracking observations of the surface flows of Jupiter (e.g., Salyk et al 2006;Ingersoll et al 2021;Duer et al 2021), which show that the observed Reynolds stresses are consistent with a direct flux of angular momentum from the eddies into the jets. The corresponding upscale energy flux from the eddies to the jets is about three times stronger than the eddy-eddy upscale flux (Young & Read 2017) and thus supports the idea of primarily a direct driving.…”
Section: Direct Drivingsupporting
confidence: 90%
“…This picture is usually connected to deep-shell simulations of rotating convection (e.g., Aurnou & Olson 2001;Christensen 2001;Heimpel et al 2005;Kaspi et al 2009;Gastine & Wicht 2012;Yadav & Bloxham 2020). It is consistent with cloud tracking observations of the surface flows of Jupiter (e.g., Salyk et al 2006;Ingersoll et al 2021;Duer et al 2021), which show that the observed Reynolds stresses are consistent with a direct flux of angular momentum from the eddies into the jets. The corresponding upscale energy flux from the eddies to the jets is about three times stronger than the eddy-eddy upscale flux (Young & Read 2017) and thus supports the idea of primarily a direct driving.…”
Section: Direct Drivingsupporting
confidence: 90%
“…Predicting the structure and the dynamics of atmospheric circulation in Uranus and Neptune (both zonal and meridional) is crucial for understanding their heat transfer mechanisms (Podolak et al 2019;Vazan & Helled 2020;Hill et al 2021) and in turn their composition and vertical mixing of molecules (Nettelmann et al 2013;Fletcher 2021;Bailey & Stevenson 2021), generation of secondary magnetic fields via their interaction with zonal winds (Cao & Stevenson 2017;Soyuer & Helled 2021), and molecular advection phenomena (e.g., like those recently shown in Jupiter with ammonia; Duer et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Work on the MWR results continues. Duer et al (2021) show evidence of downwelling below the zones from 1.5 to 240 bars, with 16 belt-zone pairs from −60 to 60 latitude. Fletcher et al (2021) documents an ammonia minimum near the 5-bar level, and Guillot et al (2020) explains how some ammonia might escape detection at that level.…”
mentioning
confidence: 95%